Study on the rock‐breaking effect of water jets generated by self‐rotatory multinozzle drilling bit - Yanbao Liu (Energy Science & Engineering, 2020)
Abstract Underground radial drilling technique is a novel hydraulic stimulation technology, which is one of the important ways to realize precise, intelligent, and efficient extraction of the gas resources. There are many factors influencing the hole‐forming effect by water jet, such as nozzle arrangement and so on. Recently, the self‐rotatory multinozzle drilling bit is frequently used to improve the rock‐breaking effect of water jets. In this paper, to study the effects of inclination angle of forward nozzles and standoff distance, the ANSYS FLUENT combined with RNG turbulence model was adopted to analyze the multinozzle jets flow field. The results indicate that the components of axial velocity and tangential velocity of forward nozzle jets are different with inclination angles of forward nozzles. Moreover, there exists an optimal standoff distance of multinozzle drilling bit for rock breaking. Besides, the drilling test was conducted using the self‐developed drilling simulation system to investigate the effect of inclination angle, radial angle, standoff distance, and jet pressure on the rock‐breaking effect of water jet. Based on the rotating characteristic of rotary jet, the asymmetric inclined linear nozzle arrangement was proposed for the multinozzle drilling bit. And the results also show that the drilling bit with three forward nozzles has larger rock‐breaking zone in terms of jetted hole diameter. Besides, the depth of jetted hole decreased, while the hole diameter increased with the inclination angle of forward nozzle.